Research Paper on Impact of Demonetization is the Uses of Plastic Money with Special Reference to Steel City Hisar: Understanding the Awareness and Usage Patterns of Plastic Money in a Changing Economic Landscape: A Case Study of Hisar District, Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Our society is moving into a brand new era where money is outlawed and a cashless society is turning into a truth? The India government is continuously introducing reforms to improve the usage rate of plastic money, to meet the changing needs of the economy, and to satisfy the demands of the consumer and wholesale market. Time requires the change in usage of hard money as with time composition of digitalization, technology and environment is changing with which citizens should adapt with for the progress of country. Keeping all this in mind government is arranging different programmes for awareness and usage of plastic money. Researcher has tried to find out awareness and frequency of usage of plastic money through a questionnaire filled from two hundred (N=200) respondents from rural and urban areas of Hisar district of Haryana. It was found that awareness differs on basis of demographics and even frequency of usage of plastic was found to be lower than awareness .Which are the main problem facing by the people?